Flight Regulations During New Normal - Djohar Djohar; Susanty I Mutiah S; Andi Pasong; Dety Junita Sulanjari (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2022)
The abolition of PCR and antigen tests as a mandatory requirement for domestic travelers invites pros and cons among the public, this study aims to determine public perceptions of the abolition of PCR and antigen tests. The location of this research is the city of Makassar, South Sulawesi Province, while the informants in this study are the general public, especially people who live in the South Sulawesi area who have traveled domestically during the COVID-19 pandemic. The data collection techniques in this study are data collection, data condensation, data presentation, and data verification or conclusions. Furthermore, the results showed that the public's perception of the abolition of PCR and antigen tests on average accepted the policies implemented by the government. This research can be used as reference material regarding the abolition of old policies and replacement with new policies in the midst of a pandemic, because previous studies have discussed changes or changes in policies under normal conditions.